Computerisation of Records in Stores Managment in Small and Medium Enterprises in Mukono: Case Study of Colline Hotel - Francis, Loro (Mukono : Uganda Christian University, 2009)
Discriptive Cataloguing Uganda Christian University BLIS
Includes references and appendix
Keywords: Records Management